Revitalisation and Innovation Based on Tradition as a Strategy for Cultural Sustainability Through Film Media - Dara Bunga Rembulan; Ika Sartika; Bonny Buntoro; Firman Pribadi; Een Herdiani (Journal of World Science, 2026)
This study explores revitalisation and tradition-based innovation as strategic approaches to achieving cultural sustainability through film media. In the era of globalization and rapid technological progress, local cultural values face challenges in maintaining relevance, particularly among younger generations. Revitalisation refers to the process of restoring traditional meanings and values, while innovation introduces new ways of expressing them within modern contexts. Film serves as a powerful medium to revive traditions through emotionally engaging and visually creative narratives that bridge the past and present. Using SWOT analysis and a strategic framework, the study highlights the importance of cross-disciplinary collaboration, digital cultural archives, and ethical representation in film production. Drawing from cultural studies and visual anthropology, it concludes that cultural sustainability can be achieved when traditional values are revitalised through creative innovation that resonates with contemporary audiences.